(untitled) (Research, Society and Development, 2020)
This work aims to show the average number of students per high school class (EM) in three municipalities in the State of Amapá, located in the North of Brazil and what are the possible causes of the variation in values during the period investigated, as well as seeking to reflect on the pros and cons of stocking policies for high school students in the state. Methodologically, this research involves mixed methods, with a quantitative and qualitative approach, using the technique of document analysis, as well as bibliographic research. The results showed that in Amapá, in the municipalities of Macapá, Santana and Laranjal do Jari, they seek to achieve the goal of universal access to education for young people aged 15 to 17, however, these policies only occur mainly from the point of view of improvement access and permanence, the construction of the student as a whole is often left out of the process. We conclude that future research that addresses and deepens the theme of this article, can provide scientific knowledge to corroborate the need for future educational improvements, combining quantitative and qualitative advances in education in the northern region of Brazil, specifically in the State of Amapá.